2021
DOI: 10.31128/ajgp-09-20-5631
|View full text |Cite
|
Sign up to set email alerts
|

How do Australian general practitioners spend their time? A cross-sectional analysis of Medicine in Australia: Balancing Employment and Life (MABEL) data examining ‘non-billable workload’

Abstract: Background and objectiveWhile Australian general practitioners (GPs) gain most of their income from direct patient interactions, they also spend time attending to professional or practice responsibilities. The aim of this study was to determine the time Australian GPs spend on work away from direct patient care ('non-billable work'), and practice and practitioner factors associated with non-billable work. MethodsThis study was a cross-sectional analysis of GPs practising >7.5 hours/week in the 2016 Medicine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…M-CHooSe nurses reported that the most frequent services they performed were also time-consuming to complete. Many of the service themes were delivered without the patient being present or remunerated according to the Medicare Benefits Schedule;for example, assisting with social services paperwork, assisting with patient transport arrangements, or chasing up paperwork from hospitals, and advocating for inclusive care such as booking interpreters (Brown et al 2021). These activities are consistent with delivering quality care; it ensures continuity of care, whole-person care, and addresses social determinants of health (Valaitis et al 2017;Thomas et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M-CHooSe nurses reported that the most frequent services they performed were also time-consuming to complete. Many of the service themes were delivered without the patient being present or remunerated according to the Medicare Benefits Schedule;for example, assisting with social services paperwork, assisting with patient transport arrangements, or chasing up paperwork from hospitals, and advocating for inclusive care such as booking interpreters (Brown et al 2021). These activities are consistent with delivering quality care; it ensures continuity of care, whole-person care, and addresses social determinants of health (Valaitis et al 2017;Thomas et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These activities are consistent with delivering quality care; it ensures continuity of care, whole-person care, and addresses social determinants of health (Valaitis et al 2017;Thomas et al 2018). However, the lack of remuneration, time and support required to complete these tasks currently discourages PHPs and leads to under-serving this population, and where tasks are attempted, risks decreasing PHP satisfaction and leads to frustration and burnout (Suphanchaimat et al 2015;Brown et al 2021). As M-CHooSE funding is not fee-for-service (non-contingent), nurses can be responsive to patient needs in ways time-based and activitybased care are not (Phillips et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Administrative burdens in Dutch healthcare have been increasing for decades, despite all initiatives to reduce them (Veenendaal et al, 2008;Joldersma et al, 2016;Ministry of VWS, 2018;Lint, 2019;Hanekamp et al, 2020;Keuper et al, 2022). Foreign healthcare institutions face the same problem (Cebul et al, 2008;Brown et al, 2021;Chernew & Mintz, 2021). This has a serious negative impact on the functioning and satisfaction of healthcare staff (V&VN, 2019) and is one of the most frequently cited reasons for resigning (Ahli, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Before the COVID-19 pandemic, 40% of the working time was spent on administrative tasks and despite all the improvement initiatives, this burden have increased for decades (Veenendaal, Waardenaar and Trappenburg, 2008;Joldersma, Laarman-Wierenga and Brink, 2016;Ministry of VWS, 2018;Lint, 2019;Hanekamp, Heesbeen and Taks, 2020;Keuper, Batenburg and Verheij, 2022). Various studies indicate that this problem is an international issue (Cebul et al, 2008;Brown, Enticott and Russell, 2021;Chernew and Mintz, 2021). This issue has a severe impact on the functioning and satisfaction of healthcare staff (V&VN, 2019) and appears to be one of the reasons for resigning (Ahli, 2019).…”
Section: Introductionmentioning
confidence: 99%